PENGARUH BERBAGAI MEDIA TANAM TERHADAP PERKECAMBAHAN DAN PERTUMBUHAN VEGETATIF TANAMAN PEPAYA (Carica papaya L) - Farida, Farida (Jurnal Magrobis, 2017)
The effect of various planting media on germination and vegetative growth of papaya plant. The research was conducted to analysis media tanam treatment of carica papaya germination and seed growth resfectively. Experiments were hold in Sangatta, East Kutai, East Kalimantan on October 2015 to April 2016 period. The experiments was conducted in the non factorial experiments on Completely Randominazed Design (CDR) with three replications. The factor is growing media treatment (M) : m1 = top soil, m2 = sand, m3 = saw-dust, m4 = shell, and m5 = soot. The result showed significantly on the procentation of germination, speed of germination, and seed growth. m3 treatment showed the best on the procentation of germination is 74,00%, the speed of germination is 17,40 day, and seed growth is 9,72 cm.Key word : Growing media, Papaya, Growth